A study of occupational stress and workplace spirituality in Himachal Pradesh police - Kaushal, Shyam and Jalan, Stuti (Productivity : A Quarterly Journal of The National Productivity Council)
Occupational stress has become pervasive in nearly all workplaces. The negative effects of occupational stress have become a serious concern for the management. They constantly endeavour to take initiatives in order to control stress. Policing has been identified to be one of the most stressful occupations. Numerous studies have identified the level and sources of job stress in police which result in lower productivity and efficiency of the individuals. Lately, workplace spirituality has been identified to improve the overall functioning of an organization. The study attempts to examine the relationship and impact of workplace spirituality on occupational stress in H.P. police. The study was conducted on 118 police personnel from Shimla and Solan districts of Himachal Pradesh. The results of the study showed that there exists a negative and significant relationship between occupational stress and workplace spirituality. The study also revealed a significant impact of workplace spirituality on occupational stress. Amongst them, sense of community and alignment of organizational values had the most significant impact on occupational stress. Lack of alignment of organizational values was identified as the major cause which resulted in low workplace spirituality. It is suggested that efforts should be taken to strengthen the alignment between organizational and individual values. Also, the decision makers in the state police should focus on nurturing the spiritual aspect of police personnel at workplace in order to control stress. - Reproduced
Keywords: Occupational stress, Workplace spirituality, Office politics, Organization, corporate culture